Pencucian Uang dalam Era Globalisasi Tantangan dan Penanganannya di Indonesia - Cumbrandika, Chitto; Satria, Naufal Ghozi; Ihsana, Nurmalia (HUMANIORUM, 2024)
In the era of globalization marked by advances in telecommunications and transportation technology, the phenomenon of money laundering has become a challenge that crosses national boundaries. This article discusses the role of the legal system, international cooperation, and strict supervision of the financial sector in tackling money laundering practices. This research uses a qualitative approach with a focus on legal policy analysis and regulatory interpretation. This research adopts a qualitative approach with a focus on legal policy analysis and regulatory interpretation. Data was obtained through literature studies which included books, scientific publications, and primary and secondary legal sources. A regulation-based approach is used to explore all regulations related to the legal issues studied. The increasing intensity of money laundering crimes in the context of globalization emphasizes the need to strengthen the legal and regulatory system. International cooperation is key to overcoming this challenge. Strict supervision of the financial sector, including banking and related financial institutions, is necessary to prevent money laundering practices. Furthermore, effective handling of money laundering requires joint efforts between law enforcement officials, the private sector, and financial institutions. A deep understanding of developments in communications technology and financial systems is also key in dealing with this phenomenon.